Prognostic value of left ventricular global longitudinal strain in patients with moderate aortic stenosis. (4th February 2022) - Stassen, J; Pio, SM; Ewe, SH; Singh, GK; Hirasawa, K; Butcher, SC; Marsan, NA; Delgado, V; Bax, JJ
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): ESC Training Grant App000064741 Background Impaired left ventricular (LV) global longitudinal strain (GLS) is associated with worse outcomes in patients with severe aortic stenosis, but its prognostic value in patients with moderate aortic stenosis (MAS) is largely unknown. Purpose To investigate the prognostic implications of LV GLS in patients with MAS and preserved LV ejection fraction (EF). Methods: LV GLS was evaluated by speckle tracking echocardiography in 621 patients (age 71 ± 12 years, 59% men) with MAS (aortic valve area 1.0 – 1.5cm2) and preserved LVEF (≥50%). Impaired LV GLS was defined as an LV GLS value <16%, based on spline curve analysis (i.e. where the hazard ratio for all-cause mortality was ≥1). Clinical outcomes were defined as all-cause mortality and a composite endpoint of all-cause mortality and aortic valve replacement. Results Patients with LV GLS <16% (n = 282) were significantly older, more likely to be male and had more comorbidities (diabetes mellitus, atrial fibrillation, more impaired renal function) compared to patients with LV GLS ≥16% (n = 339). In terms of echocardiographic data, patients with LV GLS <16% had larger LV volumes, lower LVEF and higher E/e'. During a median follow-up of 53 (27 – 102) months, 199 (32%) patients died. For the composite endpoint, 409 patients (66%) underwent AVR (n = 290) or died (n = 119) during a median follow-up of 29 (IQR 14 – 54) months. Patients with LV GLS <16% experienced significantly lower survival rates (p < 0.001) and event-free survival rates (p = 0.001) compared to patients with LV GLS ≥16% (Figure 1). On multivariable analysis, LV GLS was independently associated with all-cause mortality (HR 2.442; 95% CI: 1.762 – 3.384; p < 0.001) and the composite endpoint of all-cause mortality and aortic valve replacement (HR 1.862; 95% CI: 1.498 – 2.315; p = 0.040) (Figure 2). Conclusions In patients with MAS and preserved LVEF, reduced LV GLS is associated with an increased risk of all-cause mortality and the composite endpoint of all-cause mortality and AVR. Assessment of LV GLS may be useful in the risk stratification of these patients.